ETIKA BISNIS ISLAM PADA SKEMA KREDIT AKULAKU DI BISMAR PROBOLINGGO - Muhammad Abdul, Yunus; Ibban Muhammad Yusal; Reza Hilmy Luayyin (Wasīlah: Journal Of Sharia Sciences, 2026)
This study examines the practice of digital credit financing through the Akulaku application for laptop purchases at the Bismar Probolinggo Store from the perspective of the qardh contract and Islamic business ethics. The paylater service offered by Akulaku makes it easier for consumers to meet their electronic needs, but on the other hand, raises Islamic legal issues related to additional fees, late fees, and clarity of the contract object. This study uses a qualitative approach with field research. Data were obtained through interviews, observation, and documentation, then analyzed using descriptive-analytical methods based on the principles of muamalah fiqh and Islamic business ethics. The results show that Akulaku practices in Bismar Probolinggo contain several sharia issues, particularly the discrepancy between the contract object listed in the application and the goods received by consumers, which has the potential to contain elements of gharar and contract manipulation (hilah). Furthermore, the application of additional fees and late fees has the potential to approach the practice of riba qardh. These findings emphasize the importance of contract clarity, transaction transparency, and oversight of sharia ethics in digital financing practices to align with the principles of justice and honesty in Islamic law.